Hearing screening in newborns: systematic review of accuracy, effectiveness, and effects of interventions after screening. Issue 2 (26th March 2009) - Wolff, R; Hommerich, J; Riemsma, R; Antes, G; Lange, S; Kleijnen, J
Abstract : Background: The authors aimed to evaluate the benefits and harms of universal newborn hearing screening programmes in the detection of hearing impairment. Objectives: In the absence of randomised trials evaluating whole screening programmes, the study divided the objective into three systematic reviews of non-randomised controlled studies of diagnostic accuracy of screening tests, screening versus no screening, and therapeutic effect of early versus later treatment. Methods: The authors searched 11 bibliographic databases, and included 17 studies (diagnostic: 9, screening: 2, and treatment: 6). All studies apart from one treatment study showed major quality deficits. Eight diagnostic studies comparing otoacoustic emissions with auditory brainstem response showed sensitivities (and specificities) between 50% (49.1%) and 100% (97.2%). Results: The studies comparing screening versus no screening showed an improvement of speech development of children in the screening group compared with the group without screening. Early treatment was associated with better language development in comparison to children with later treatment. Conclusions: The authors concluded that there is a lack of high-quality evidence regarding all elements of newborn hearing screening. Early identification and early treatment of children with hearing impairments may be associated with advantages in language development. Other patient-relevant parameters, such as social aspects, quality of life, and educational development, have not been adequately investigated.